Pancreatic trypsin enzymatic activity in broilers which intake royal palm nut meal - Martínez-Pérez, Madeleidy; Vives Hernández, Yesenia; Alberto Vázquez, Maryen; Hernández Lemus, Susan K. (Cuban Journal of Agricultural Science, 2025)
To study the pancreatic trypsin enzymatic activity in broilers which intake royal palm nut meal, a total of 40 animals (HE21) distributed in a completely random design were used. Four treatments were designed: control and inclusion of 5, 10 and 15 % royal palm nut meal. The animals were weighed and sacrificed at 42 days and the pancreas were extracted, they were weighed and expressed relative to live weight and the trypsin enzymatic activity was determined, which increased with the inclusion of 5 and 10 % compared to the control and 15 % (5744.50 and 5131.50 vs 2415.67 and 1540.67 mg of released tyrosine. min-1. mg-1 of protein, respectively). It is concluded that the inclusion of royal palm nut meal up to 10 % in broilers diets increase the pancreatic trypsin enzymatic activity to digest proteins in the gastrointestinal tract.